Prostitution and Women Empowerment’s Role - Cikitta Nova Khanza; Olga Maharani Yuvia; Imam Al Rezki (Institut Pariwisata dan Bisnis Internasional, 2015)
The feminist movement has been admitted by the society, which is bringing the positive changes for the women. Over the time, the paradigm of women’s role in society has been changed because nowadays the women has been entered the job sectors that used to be dominated by men. It cannot be denied that this feminist movement has developed since the 18 century, which has become the sign of the opening of public space for the women. This journal will investigate the influence of women empowerment towards the prostitute workers and their health in Pasar Kembang, Yogyakarta. Because these days, the role of the women has becoming special attention through the various jobs that done by women especially women who participate in the dark industry one like sex tourism which is still being controversial through the women’s role.